Construction and catalytic activities of polyoxometalate-based compound containing helical chains. Issue 3 (1st February 2017) - Sha, Jing-Quan; Yang, Xi-Ya; Sun, Long-Jiang; Li, Shu-Xian; Sheng, Ning; Li, Ji-Shen
Abstract: A polyoxometalate-based, inorganic–organic hybrid compound containing a helical structure along the a axis, [Ag(pyttz)2 ][H2 PW12 O40 ]·2H2 O ( p- pyttz = 3-(pyrid-4-yl)-5-(1H-1, 2, 4-triazol-3-yl)-1, 2, 4-triazolyl), has been isolated and structurally characterized. Single-crystal X-ray diffraction analysis reveals that the new compound possesses two helical channels constructed by the left- and right-handed helical chains, respectively, which are fused together through sharing POMs dimer fabricating a 3-D framework with 4 4 ·5 3 ·6 3 4 4 ·5 3 ·6 3 topolopy. The new compound displays good acid-catalytic activity toward the synthesis of Aspirin and good oxidation-catalytic activity to the decomposition of Rhodamine B dye; the catalytic reaction kinetics are discussed. Abstract :